Irving Fisher, Inflation, and the Nominal Rate of Interest - Choate, G. Marc; Archer, Stephen H. (Journal of Financial and Quantitative Analysis, 1975)
G. Marc Choate, Stephen H. Archer, Irving Fisher, Inflation, and the Nominal Rate of Interest, The Journal of Financial and Quantitative Analysis, Vol. 10, No. 4, 1975 Proceedings (Nov., 1975), pp. 675-685